In-situ generated Mn3O4-reduced graphene oxide nanocomposite for oxygen reduction reaction and isolated reduced graphene oxide for supercapacitor applications - Jha, Plawan Kumar; Kashyap, Varchaswal; Gupta, Kriti; Kumar, Vikash; Debnath, Anil Krishna; Roy, Debashree; Rana, Shammi; Kurungot, Sreekumar; Ballav, Nirmalya (Carbon, 2019)
We have generated in situ nanocomposite of Mn3O4 and reduced graphene oxide (rGO) upon employing wet-chemical reduction of graphene oxide (GO) by Mn(II) salt as mild-reducing agent for the first time and examined the oxygen reduction reaction (ORR) activity in 0.1 M KOH electrolyte. The half-wave potential (E-1/2) of the nanocomposite catalyst (20% Mn3O4-rGO/C) was found to be around -0.153 V which is only similar to 87 mV negative from the commercially available catalyst (20% Pt/C). Remarkably, after 5000 linear sweep voltammetry cycles the E-1/2 shifted marginally by 20 mV; and the number of electrons transferred during ORR was estimated to be close to 4. Such an efficient electrocatalytic performance of the nanocomposite was primarily attributed to the synergistic interaction between Mn3O4 and rGO. The fabricated all-solid-state supercapacitor of rGO (extracted from the nanocomposite) in aqueous polyvinyl alcohol-sulfuric acid (PVA-H2SO4) gel polymer electrolyte (GPE) showed C-s value of similar to 310 F/g at a current density of 1 A/g along with long durability (10,000 charge-discharge cycles). All-solid-state flexible rGO supercapacitor exhibited high-flexibility and excellent durability (30,000 cycles with 100% retention of C-s). Our results provide an enormous opportunity in designing transition metal oxides decorated semiconducting reduced graphene oxide nanocomposite platforms for various electrochemical applications. (C) 2019 Elsevier Ltd. All rights reserved.

Integrating structurally perfect s=1/2 kagome-lattice with reduced graphene oxide - Gupta, Kriti; Dadwal, Arun; Ninawe, Pranay; Joy, Pattayil A.; Ballav, Nirmalya (Journal of Physical Chemistry C, 2020)
S = 1/2 kagome-lattice hydroxychlorides are promising candidates for realizing the elusive quantum spin liquid (QSL) state. Herbertsmithite [Cu3Zn(OH)(6)Cl-2], a naturally occurring hydroxychloride mineral from the class of atacamites {[Cu-4-xMx(OH)(6)X-2] where M = Zn, Cu, Co, Ni and X = Cl, Br, I}, is one of the most appealing systems to study the QSL state because of the presence of a structurally perfect S = 1/2 kagome-lattice. It is an electrical insulator. However, realizing phase-pure herbertsmithite without imposing harsh reaction conditions remained synthetically challenging. In this work, for the first time, we have synthesized phase-pure herbertsmithite as well as its structural analogue paratacamite, [ZnxCu4-x(OH)(6)Cl-2; 0.33 = x < 1], at ambient reaction conditions. Furthermore, taking graphene oxide (GO) as an additional precursor in the reaction mixture, we have successfully integrated phase-pure crystallites of herbertsmithite (H) and paratacamite (P) with nanosheets of semiconducting and diamagnetic reduced graphene oxide (rGO) by in situ oxidation-reduction reaction. The isolated H-rGO and P-rGO systems were found to be magnetic semiconductors inheriting strong spin frustration from H and P, and semiconductivity from rGO. The H-rGO system in particular exhibited negative Seebeck coefficient (n-type semiconductor) with a thermoelectric power factor of 0.1 mu W center dot m(-1)center dot K-2 at 400 K. We anticipate the simple chemical principles outlined in this work to be useful for studying a variety of complex QSLs including electron doping. Also, semiconducting and rather unconventional materials of such metal oxochlorides with rGO isolated here need further exploration in view of thermoelectric applications.